2017
DOI: 10.1155/2017/1907952
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte CYP2B6 Can Be Expressed in Cell Culture Systems by Exerting Physiological Levels of Shear: Implications for ADME Testing

Abstract: Cytochrome 2B6 (CYP2B6) has substantial clinical effects on morbidity and mortality and its effects on drug metabolism should be part of hepatotoxicity screening. Examples of CYP2B6's impacts include its linkage to mortality during cyclophosphamide therapy and its role in determining hepatotoxicity and CNS toxicity during efavirenz therapy for HIV infection. CYP2B6 is key to metabolism of many common drugs from opioids to antidepressants, anesthetics, and anticonvulsants. But CYP2B6 has been extremely difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Cubilin is the classic example: the protein is so stable that there is scant RNA signal, to the point that investigators had to resort to embryonic tissue to find enough RNA signal to clone it [52]. Similarly, it is no surprise that expression changes in individual genes observed by other groups are absent in our analysis due to differences in cell type, method, timing, and intensity of shear stress application, and choice of renal proximal tubular cell homolog [2,20]. Importantly for drug sensitivity studies, all the drug transporting channels were preserved, except for a small decrease in ABCG2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cubilin is the classic example: the protein is so stable that there is scant RNA signal, to the point that investigators had to resort to embryonic tissue to find enough RNA signal to clone it [52]. Similarly, it is no surprise that expression changes in individual genes observed by other groups are absent in our analysis due to differences in cell type, method, timing, and intensity of shear stress application, and choice of renal proximal tubular cell homolog [2,20]. Importantly for drug sensitivity studies, all the drug transporting channels were preserved, except for a small decrease in ABCG2.…”
Section: Discussionmentioning
confidence: 99%
“…One area ripe for the application of cell spinpod culture is liver and kidney toxicity-each representing major obstacles for safe drug development [2,20]. There are well-established, FDA-approved, high throughput screens for hepatotoxicity, but none for nephrotoxicity [64,65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their work indicated variation in spheroid size over the one‐week culture period, indicating spheroid loss and merging (Baraniak & McDevitt, 2012). Hammond and Birdsall (2017) and Roy, Washizu, Tilles, Yarmush, and Toner (2001) have suggested that the shear force experienced by the cells in suspension culture may introduce phenotypic and functional changes and can hinder cell differentiation and cause cell death. We found that the suspension culture method formed fewer, larger hASC spheroids over the culture period through merging the spheroids together (Figures 6 and 7), but did not result in any significant loss of spheroids or detriment to their adipogenic differentiation (Figures 4 and 5) likely due to the low rotational speed used in our work.…”
Section: Discussionmentioning
confidence: 99%